Wild and Cultivated Cherries – Antioxidant Capacity Analysis - Topolov, Marian; Dermendjiev, Tihomir; Phortunov, Stanislav (European Scientific Journal, ESJ, 2017)
Cherries are fruit that is rich in powerful antioxidants (anthocyanin) and many different stimulating good health substances. SCOPE: Determination and analysis of pH, total phenols, antioxidant activity (radical trapping activity) total anthocyanin of wild growing and cultivated varieties of cherries. Research Methods Applied: - Systematic approach and critical analysis of the available scientific periodicals; - Spectrophotometric method for determination of adsorption and standard Gallic acid; - DPPH method for determining the antioxidant activity (radical trapping activity). The results presented are the mean values of at least three parallel tests. The total phenols of the samples we studied are in the range of 0.57 to 1.67 mg GAE / g fresh weight. Total anthocyanin in the samples we tested was in the range of 0.02 to 0.44 mg / g of fresh weight. Antioxidant activity of 7.88 to 16.20 mol TE / g fresh weight pH of 3.70 to 4.19. CONCLUSION: Common anthocyanin is highest in early sorts of cultivated cherries. In later ripening varieties of cultivated cherries, the value of common anthocyanin is significantly lower. In addition, this indicator depends on the altitude of the cultivated cherry. The antioxidant activity is highest in the variety Wild Cherry (Banya, Karlovo), Early Cherry Van (Radilovo), Van variety (Isperihovo) and Cartilage Bing variety or Bigato Burla (Novo Selo). Therefore, this indicator depends on the altitude and ripening time of the fruit.